PKM Pelatihan Media Modifikasi Pendidikan Jasmani Bagi Guru-Guru Pendidikan Jasmani Olahraga Dan Kesehatan SD Di Kecamatan Cina Kabupaten Bone - Muliadi Muliadi; Sudirman Sudirman; Abd. Kadir A. (DEDIKASI, 2020)
The purpose of PKM training in the modification of Physical Education media for the KKG PJOK SD in the Cina sub-district of Bone Regency is to make learning media / teaching aids as a way to increase teacher professionalism and overcome the problem of limited physical education facilities. Training on making physical modification media for Physical Education has 2 output targets. The first is targeting SD Penjas teachers in Cina sub-districts to be able to design / design modified Physical Education media from used materials / goods, with various types according to the teaching material. The second target is skilled teachers to make modified Physical Education media in elementary schools that are attractive, effective, and efficient in their use in learning PJOK in SD.The methods used in service activities are: 1) Lecture to deliver; Basic concepts of modification media, Modification Objectives, Utilization of Modified Media for Physical Education learning, as well as materials for Design Development and Types of Physical Education learning media in SD. 2) The demonstration is used with the hope that participants can practice how to design used materials / goods to make modified physical education media in elementary schools. To further optimize the implementation of the training, assistance is provided by the service team, namely designing and making attractive and effective modification media of Physical Education according to the teaching materials of PJOK in SD, 3) Questions and Answers, used to respond to various obstacles faced by teachers in designing / designing, making modification media Physical Education and 4) Practices / simulations or trials of using the Modified Physical Education media in SD. The participation of partners during the training shows a responsive and active attitude in asking questions and completing tasks given by the service team. The results achieved by partners are showing motivation, knowledge and understanding so that they are able to design / design and make modified Physical Education media from used goods. Although in general the teachers are still constrained by several things; not used to making interesting media, time is very limited because of the many main tasks and other tasks; Sports coach, Scout, and so on. However, through this training it can provide knowledge in designing modified Physical Education media and make and use it to help teachers and students in the learning process to improve the quality of PJOK learning in SD sub-district Cina, Bone district